Secret Message Hiding in WAVE PCM Sound File - Raja Salih; Zaid Sadiq naama; Sherna Aziz Tome (Journal of Madenat Alelem University College, 2015)
Communications today has been done among millions of users using many application devices like internet or satellite communication channels, the services they can transform many varieties of files like text, images, videos, and audio among different places. Therefore the security of data has been of extreme importance in today’s information-based society, including the fields of military, diplomacy, corporation, medicine, and etc…. A form of data hiding is steganography, which is contemporary way for protecting the information by embedding data into digital media for the purpose of copyright, and sending secret messages. In this paper a scheme of steganography system for hiding secret text message in audio file WAV, (Windows Audio Visual) format is proposed, the hiding mechanism was based on using Low-Bit Encoding (LSB) Least Significant Bit substitution techniques. To support the immunity of the hiding system, encryption methods with some other support methods (i.e., hiding and hopping) were added to the proposed hiding system, a pseudo random number generator has been designed and implemented to generate non-uniform integer jumps between successive hiding events. The jumps mechanism of the suggested generator is based on the linear feedback shift register of length 23 with feedback function F(x)=1+X+X23 produce the maximum period 223-1= 8388607.